Modeling the Electrical Impedance of Epoxy Polymer/Carbon Black Composite Materials - Z. Samir; R. Belhimria; S. Boukheir; M. E. Achour; L. C. Costa (Jordan Journal of Physics, 2025)
The effect of filler aspect ratio on the dielectric properties of epoxy resin reinforced with carbon black (CB) is here investigated. The composites change from an electrical insulator to a conductor as the CB content is increased from 1.5% to 4.5%, which is called the percolation region. Complex impedance spectra and Bode diagrams of these composites were carefully analyzed and the corresponding equivalent circuits (EC) under different concentrations of CB were also provided. Furthermore, the correlation between the shape of Bode diagrams and the equivalent circuits was discussed. Finally, the Cole–Cole representation was used to interpret the impedance spectra of all the samples. Keywords: Carbon black, Percolation, Complex impedance, Bode diagram, Cole-Cole.